Effect of abiotic stress on carotenoids accumulation in pumpkin plants and callusses under light and dark conditions - Shahidan, Norshazila; Othman, Rashidi; Jaswir, Irwandi; Hashim, Yumi Zuhanis Has-Yun (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Pumpkin is abundantly planted in Malaysia and very rich with carotenoid compounds that can support healthy living due to its antioxidant properties. However, the research on its carotenoid compound has not received the attention it deserves, either from researchers or government. This research was conducted to study the effect of abiotic stress on the carotenoids accumulation through in pumpkin plants and calluses under light and dark conditions. The abiotic stresses used in this study were Ultra Violet light exposure, Polyethylene Glycol 4000, Jasmonic Acid, Salicylic Acid and Murashige and Skoog Salt. It was found that exposure to Ultra Violet light could improve the purity of lutein compound in pumpkin leaves with the absence of β-carotene. Salicylic Acid treatment under light condition was found to improve the lutein compound to ten times higher than the controlled treatment in pumpkin stems. The highest yield of β-carotene compound in pumpkin calluses was detected in half strength treatment under light condition. Even though the carotenoid compound in pumpkin plants and calluses could be improved with the treatments mentioned above, the mechanisms involved regarding the treatment effects on carotenoid biosynthesis has not been well studied. Thus, further study should be conducted to understand the mechanisms better.